SEJARAH PENCETAKAN AL-QUR`AN DI JAWA TENGAH - Ahmad Saifudin (Wahana Islamika: Jurnal Studi Keislaman, 2021)
The purpose of this research is to find out thehistory of Qur’anic printing in Central Java. This is motivatedby differences between previous researchers in terms ofdetermining the company that printed the Qur`an first inCentral Java. Some mentioned PT Thoha Putra Semarang andsome others mentioned PT Menara Kudus. The difference ofopinion arises because the data they use is not primary data.This research method uses historical research. Apart from PTMenara Kudus and PT Thoha Putra Semarang, this researchdata was also obtained from PT Tiga Serangkai Solo; as aform of continuation of the history of printing the Koran inCentral Java. The data obtained and processed in this studyare primary data, namely manuscripts printed by the threecompanies and interviews with directors or managers ofthese companies. The results of this research that PT MenaraKudus was the first company to print the Qur`an in CentralJava, in 1959. Then it was followed by PT Thoha PutraSemarang in 1977. The development of printing the Qur`ancontinued until now, even more crowded with the presenceof companies that were not involved in the world of printingthe Qur`an, then participated in printing the Koran. This canbe seen from the manuscripts printed by PT Tiga SerangkaiSolo which look more contemporary.